Complete Genome Analysis of Highly Pathogenic Non-O1/O139 Vibrio cholerae Isolated From Macrobrachium rosenbergii Reveals Pathogenicity and Antibiotic Resistance-Related Genes - Zhou, Yifan; Gu, Shuwen; Li, Jie; Ji, Peng; Zhang, Yingjie; Wu, Congcong; Jiang, Qun; Gao, Xiaojian; Zhang, Xiaojun (Frontiers in Veterinary Science, 2022)
Non-O1/O139 Vibrio cholerae is highly virulent pathogen that causes mass mortalities of various aquatic animals. In the present study, we sequenced the whole genome of non-O1/O139 V. cholerae GXFL1-4 isolated from Macrobrachium rosenbergii for revealing the pathogenicity and antibiotic resistance. The result showed its genome contained two circular chromosomes and one plasmid with a total size of 4,282,243 bp, which harbored 3,869 coding genes. Among them, 3047, 2659 and 3661 genes were annotated in COG, GO and KEGG databases, respectively. In addition, 372 potential virulence genes were predicted based on the VFDB database, including type II, III, IV and VI secretion systems related genes, flagella genes and pilus formation or motility related genes, etc. Blast results in the CARD database showed that the strain contained 27 categories of 148 antibiotic resistance related genes, including efflux pump complex antibiotic resistance genes and antibiotic resistance gene cluster genes, etc. The PHI database annotated 320 genes related to pathogen-host interaction, including T3SS genes, virulence regulatory factors, transcriptional regulators, two-component response regulator related genes, etc. The whole-genome analysis suggested that the pathogenic non-O1/O139 V. cholerae strain GXFL1-4 might have a complex molecular mechanism of pathogenicity and antibiotic resistance. This study provides a wealth of information about non-O1/O139 V. cholerae genes related to its pathogenicity and drug resistance, and will facilitate the understanding of its pathogenesis as well as the development of prevention and treatment of the pathogen.